2016
DOI: 10.1080/21663831.2015.1124298
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Micronanoscaled Metallic Glasses

Abstract: In this paper, research on the mechanical behavior of micronanoscaled metallic glasses (MGs) is reviewed, with an emphasis on works achieved through in situ transmission electron microscope. It was found that the strength of micronanoscaled MGs has a nonlinear dependence on sample size. Corresponding to the transition of size-dependent strength, the deformation mechanism of MGs changes gradually from brittle to ductile with the critical transition size being affected by strain rate, e-beam irradiation and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…These results are in agreement with previous MD simulation results which reported that sizeindependent shear banding until their dimensions approach the shear-band thickness which is about 5-20 nm (Adibi et al, 2016;Liontas et al, 2016;Shi, 2019). This transition appears in experiments at a lager sample diameter, between 100 and 400 nm, as compared with MD simulations (Tian et al, 2016). This difference in the sample size on the change of the deformation mode between experiments and simulations can be related to the different processing and testing conditions (Shi, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with previous MD simulation results which reported that sizeindependent shear banding until their dimensions approach the shear-band thickness which is about 5-20 nm (Adibi et al, 2016;Liontas et al, 2016;Shi, 2019). This transition appears in experiments at a lager sample diameter, between 100 and 400 nm, as compared with MD simulations (Tian et al, 2016). This difference in the sample size on the change of the deformation mode between experiments and simulations can be related to the different processing and testing conditions (Shi, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…showed that enhanced plastic deformation in Zr-based bulk metallic glasses is possible through the suppression of shear localization by using geometrical constraints [ 5 ]. Alternatively, researchers have shown that when sample dimensions are reduced to the nanoscale, homogeneous flow supersedes shear band propagation as the dominant mode of deformation and results in enhanced ductility [ 6 , 7 ]. Furthermore, molecular dynamics (MD) simulations have revealed that metallic glass films can deform plastically below a critical thickness by non-localized flow [ 8 ], providing further promise for increased ductility at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Hufnagel et al [ 48 ] have indicated that although many previous studies have focused on the deformation behavior of BMGs under uniaxial stress states, the understanding of the deformation behavior as well as structural evolution under more complex stress states is urgently needed to uncover the shear-banding mechanisms, such as the shear localization process. The research progress on the formation mechanisms of shear bands in BMGs has been summarized in many review papers [ 4 , 27 , 30 , 34 , 35 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ], however, the formation of shear bands under complex stress fields has rarely been emphasized. Here, the initiation of shear bands under more complex stress fields is summarized.…”
Section: Initiation Of Shear Bands Under Complex Stress Fieldsmentioning
confidence: 99%